2014
DOI: 10.1590/1516-3180.20141322t2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for preventing obesity in children

Abstract: BACKGROUND: Prevention of childhood obesity is an international public health priority given the significant impact of obesity on acute and chronic diseases, general health, development and well-being. The international evidence base for strategies that governments, communities and families can implement to prevent obesity, and promote health, has been accumulating but remains unclear.OBJECTIVE: This review primarily aims to update the previous Cochrane review of childhood obesity prevention research and deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
641
2
31

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 491 publications
(698 citation statements)
references
References 1 publication
19
641
2
31
Order By: Relevance
“…School infrastructure and physical environment, policies, curricula and staff have the potential to positively influence child health (40) . Whereas some school-based interventions have predominantly targeted improvements in healthy eating and physical activity by curriculum initiatives (41) , POZ offered the opportunity to enhance non-curricular education on nutrition and physical activity, involving children and families in extracurricular sessions. Studies in school-aged children which used multifaceted approaches to improving physical activity and nutrition education provided encouragement.…”
Section: Discussionmentioning
confidence: 99%
“…School infrastructure and physical environment, policies, curricula and staff have the potential to positively influence child health (40) . Whereas some school-based interventions have predominantly targeted improvements in healthy eating and physical activity by curriculum initiatives (41) , POZ offered the opportunity to enhance non-curricular education on nutrition and physical activity, involving children and families in extracurricular sessions. Studies in school-aged children which used multifaceted approaches to improving physical activity and nutrition education provided encouragement.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognised that changes in the social and economic environment in the last three decades have been a major contributor to altered eating and activity patterns resulting in positive energy balance. The most recent update to the Cochrane review of interventions for preventing obesity in children (Waters et al 2011) identified that the majority of childhood obesity prevention intervention evaluations were short-term (12 months or less) and largely focussed on individual behaviour change. Also from this review there is now some early evidence that settings-based obesity prevention interventions are effective at reducing body mass index in the short term.…”
Section: Introductionmentioning
confidence: 99%
“…Regular auditing of actual time spent being physically active should be carried out in all schools on a regular basis and ideally more sessions allocated for physical activity (92) . The introduction of a new compulsory subject combining healthy eating, physical activity and body image in secondary-school curricula may help foster healthy dietary habits and enhance overall levels of physical activity, and is a recommended component of best-practice interventions (92) . This will complement an existing scheme that aims to shape children's food preferences and promote sustainable consumption of fruit and vegetables through once-weekly distribution of free fruit and vegetables portions in primary schools (73) .…”
Section: Physical Factorsmentioning
confidence: 99%